Mechanisms of Cisplatin-Induced Ototoxicity and Otoprotection - Sheth, Sandeep; Mukherjea, Debashree; Rybak, Leonard P.; Ramkumar, Vickram (Frontiers in Cellular Neuroscience, 2017)
Evidence of significant hearing loss during the early days of use of cisplatin as a chemotherapeutic agent in cancer patients has stimulated research into the causes and treatment of this side effect. It has generally been accepted that hearing loss is produced by excessive generation of reactive oxygen species (ROS) in cell of the cochlea, which led to the development of various antioxidants as otoprotective agents. Later studies show that ROS could stimulate cochlear inflammation, suggesting the use of anti-inflammatory agents for treatment of hearing loss. In this respect, G-protein coupled receptors, such as adenosine A1 receptor (A1AR) and cannabinoid 2 receptors (CB2) have shown efficacy in the treatment of hearing loss in experimental animals by increasing ROS scavenging, suppressing ROS generation or by decreasing inflammation. Inflammation could be triggered by activation of transient receptor potential vanilloid 1 (TRPV1) channels in the cochlea and possibly other TRP channels. Targeting TRPV1 for knockdown has also been shown to be a useful strategy for ensuring otoprotection. Cisplatin entry into cochlear hair cells is mediated by various transporters, inhibitors of which have been shown to be effective for treating hearing loss. Finally, cisplatin-induced DNA damage and activation of the apoptotic process could be targeted for cisplatin-induced hearing loss. This review focuses on recent development in our understanding of the mechanisms underlying cisplatin-induced hearing loss and provide examples of how drug therapies have been formulated based on these mechanisms.